SKEMA CITRA EKSISTENSI DALAM LIRIK KAWIH SUNDA ABADI SERI 1 KARYA MANG KOKO: KAJIAN SEMANTIK KOGNITIF - Nova Azzahra; Tajudin Nur (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
Songs are means used to convey messages using beautiful lyrics and harmonious musical accompaniment. It is not uncommon for a song to often use metaphors which add a beautiful impression to the song. This research will describe the types and forms of metaphors in Mang Koko's songs. The data used is 10 Eternal Sunda Kawih Series 1 by Mang Koko. The method used in this research is Qualitative Descriptive. The theory used is the study of Conceptual Metaphor by Lakoff and Johnson (2003) and Image Schema Theory by Saeed (2003); Cruse and Croft (2004). The results of this research were found. Based on the results of identifying image schemes using theory. Based on image schemes according to Cruse and Croft, 15 identity image schemes were found which were divided into 3 Existences with the Object type, 10 Existences with the Process type, and 2 Existences with the bounded space type.